Enhanced Cartilaginous Tissue Formation with a Cell Aggregate-Fibrin-Polymer Scaffold Complex - Lee, Soojin; Lee, Kangwon; Kim, Soo Hyun; Jung, Youngmee (MDPI AG, 2017)
Cell density is one of the factors required in the preparation of engineered cartilage from mesenchymal stem cells (MSCs). Additionally, it is well known for having a significant role in chemical and physical stimulations when stem cells undergo chondrogenic differentiation. Here, we developed an engineered cartilage with a cell aggregate-hydrogel-polymer scaffold complex capable of inducing the effective regeneration of cartilage tissue similar to natural cartilage while retaining a high mechanical strength, flexibility, and morphology. Cell aggregates were generated by the hanging drop method with rabbit bone marrow stromal cells (BMSCs), and poly (lactide-co-caprolactone) (PLCL) scaffolds were fabricated with 78.3 +/- 5.3% porosity and a 300-500 mu m pore size with a gel-pressing method. We prepared the cell aggregate-fibrin-poly (lactide-co-caprolactone) (PLCL) scaffold complex, in which the cell aggregates were evenly dispersed in the fibrin, and they were immobilized onto the surface of the polymer scaffold while filling up the pores. To examine the chondrogenic differentiation of seeded BMSCs and the formation of chondral extracellular matrix onto the complexes, they were cultured in vitro or subcutaneously implanted into nude mice for up to eight weeks. The results of the in vitro and in vivo studies revealed that the accumulation of the chondral extracellular matrices was increased on the cell aggregate-fibrin-PLCL scaffold complexes (CAPs) compared to the single cell-fibrin-PLCL scaffold complexes (SCPs). Additionally, we examined whether the mature and well-developed cartilaginous tissues and lacunae structures typical of mature cartilage were evenly distributed in the CAPs. Consequently, the cell aggregates in the hybrid scaffolds of fibrin gels and elastic PLCL scaffolds can induce themselves to differentiate into chondrocytes, maintain their phenotypes, enhance glycosaminoglycan (GAG) production, and improve the quality of cartilaginous tissue formed in vitro and in vivo.
Keywords: AUTOLOGOUS CHONDROCYTE IMPLANTATION; PARTIAL-THICKNESS DEFECTS; MESENCHYMAL STEM-CELLS; ARTICULAR-CARTILAGE; BIODEGRADABLE POLY(L-LACTIDE-CO-EPSILON-CAPROLACTONE); CHONDROGENIC DIFFERENTIATION; OSTEOCHONDRAL DEFECTS; OBSERVATIONAL COHORT; REGENERATION; REPAIR